Exploring a new habitat for Distoseptispora (Distoseptisporaceae, Distoseptisporales) and introducing D. mangrovei sp. nov. from a mangrove wetland in Guangdong Province, China - Li, Hongze; Shu, Yongxin; Doilom, Mingkwan; Hyde, Kevin D.; Dong, Wei (Phytotaxa, 2026)
Species within Distoseptispora have demonstrated an exceptional rate of expansion with an ongoing investigation of lignicolous microfungi from freshwater and terrestrial habitats. In just one year (2025), a remarkable 36 species were described. However, despite the substantial increase in documented species, our understanding towards the specific/generic delimitation of Distoseptispora remains insufficient. In this study, we explored a mangrove habitat, a special aquatic habitat under salt stress, for Distoseptispora to facilitate a comprehensive understanding of this group. The specimen was collected from an estuarine mangrove wetland at the Hanjiang River in Guangdong Province, China. Multi-locus phylogenetic analysis of a concatenated LSU, ITS, tef1-α, and rpb2 dataset and morphological study identified our new collection as a novel species, Distoseptispora mangrovei. Distoseptispora mangrovei is unique by its short, solitary conidiophores and variable conidia, which are solitary or occasionally catenate, mostly elongated, obclavate, not or slightly constricted at the septa, but sometimes deeply constricted at some septa. Percurrent proliferation from cut ends of conidia is also occasionally observed.